2012
DOI: 10.1155/2012/425463
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Spirituality on Depression, Posttraumatic Stress Disorder, and Suicidality in Active Duty Military Personnel

Abstract: Understanding the role of spirituality as a potential coping mechanism for military personnel is important given growing concern about the mental health issues of personnel returning from war. This study seeks to determine the extent to which spirituality is associated with selected mental health problems among active duty military personnel and whether it moderates the relationship between combat exposure/deployment and (a) depression, (b) posttraumatic stress disorder (PTSD), and (c) suicidality in active du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
44
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 41 publications
3
44
0
1
Order By: Relevance
“…A large study among 28,546 active duty military personnel showed that spirituality buffered depression and posttraumatic stress disorders (PTSD) only among soldiers with low-moderate combat exposure (Hourani et al 2012). The authors concluded that ''the buffering role of spirituality in mental health is limited,'' and that it ''may be potentially overwhelmed by great stress, such as high levels of combat exposure'' (Hourani et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A large study among 28,546 active duty military personnel showed that spirituality buffered depression and posttraumatic stress disorders (PTSD) only among soldiers with low-moderate combat exposure (Hourani et al 2012). The authors concluded that ''the buffering role of spirituality in mental health is limited,'' and that it ''may be potentially overwhelmed by great stress, such as high levels of combat exposure'' (Hourani et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…There is also a dearth of information on the mental health status and combat experiences of those service members who seek care from chaplains. This is critical given that our previous work has highlighted the complex relationship between spirituality and mental health in veterans with various levels of combat exposure (Hourani et al, 2012). Interestingly, we have found that spirituality had a buffering effect against depression and PTSD, but only in those who had experienced low or moderate levels of combat (Hourani et al, 2012).…”
mentioning
confidence: 80%
“…This is critical given that our previous work has highlighted the complex relationship between spirituality and mental health in veterans with various levels of combat exposure (Hourani et al, 2012). Interestingly, we have found that spirituality had a buffering effect against depression and PTSD, but only in those who had experienced low or moderate levels of combat (Hourani et al, 2012). In addition to PTSD, there is emerging evidence of what is referred to as moral injury-defined as "potentially morally injurious events, such as perpetrating, failing to prevent, or bearing witness to acts that transgress deeply held moral beliefs and expectations may be deleterious in the long-term, emotionally, psychologically, behaviorally, spiritually, and socially" (Litz et al, 2009)-following combat and war, whereby veterans report challenges to their spiritual beliefs because of combat experiences (Drescher et al, 2011;Vargas, Hanson, Kraus, Drescher, & Foy, 2013).…”
mentioning
confidence: 99%
“…The association between higher levels of spirituality and lower levels of depressive symptoms has been demonstrated in several different subpopulations, including primary care outpatients (Daaleman and Kaufman 2006;Doolittle and Farrell 2004), adolescent girls (Desrosiers and Miller 2007), terminally ill patients with cancer and AIDS (Nelson et al 2002(Nelson et al , 2009, and military personnel (Hourani et al 2012). In some prospective epidemiological surveys, participants for whom spirituality was highly important (Miller et al 2012) or who have higher scores on the existential subscale of the spiritual well-being scale (Maselko et al 2009) seemed to be protected from major depression, especially relapse in those with a history of depression.…”
mentioning
confidence: 99%